Model Bacaan Anak Berbasis Kearifan Lokal - Nursalim Nursalim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This paper is generally aimed at generating an innovative multicultural-based learning model that meets the basic educational goals that can be used in schools and madrasah. Multicultural-based learning model in the form of preschool children's reading models, traditional literature, fiction, biography and autobiography, science, poetry and poetry. Reading is based on local wisdom is a reading about the cultural life of the surrounding community or area of education location. Writing a local-based story is an open story of local cultural themes. Local-based education is education that utilizes local and global advantages in economic, arts and cultural aspects, human resources, language, information and communication technology, ecology, etc. into the school curriculum which ultimately benefits the development of competencies of learners that can be utilized for competition global. Local wisdom sources are human potential, religious potential, cultural potential. While the purpose of local wisdom-based education or the advantage of providing knowledge, skills and behavior to learners so that they have a solid insight about the state of the environment and the needs of the community in accordance with the values / rules prevailing in the region and support regional development and national development. While the specific purpose of local wisdom-based education is so that students more familiar with and become more familiar with the natural environment, social, and cultural. Students have the provision of skills and knowledge and knowledge about the area that is useful for themselves as well as the community in general. Students have attitudes and behaviors that are in harmony with the values / rules that apply in the area and preserve and develop the noble values of local culture in order to support regional development and national development.